Performances of random codes based on Quasigroups for transmission of audio files - Popovska-Mitrovikj, Aleksandra; Ilievski, Vladimir; Bakeva, Verica (2015 23rd Telecommunications Forum Telfor (TELFOR), 2015)
Error-correcting codes can be applied for transmission of images and audio files through a noise channel. Application of Random Codes Based on Quasigroups (RCBQ) for image transmission is considered elsewhere. In this paper we investigate performances of these codes for transmission of audio files through a binary-symmetric channel. We present and analyze several experimental results obtained using Cut-Decoding and 4-Sets-Cut-Decoding algorithms defined for RCBQ. In the experiments we use code (72, 576) with rate 1/8. We made experiments with Beethovens "Ode to Joy".